Graceful aging and its correlates at the Ursuline Franciscan Congregation, Mangalore, India: 1988-1989 - Monteiro, Carmelita, UFS (Animo Repository, 1989)
This study aimed to find out the perceptions on graceful aging of all the sixty retired sisters of the Ursuline Franciscan Congregation. It likewise identified some possible correlates of graceful aging among the respondent sisters. Two questionnaires on graceful aging, and on the correlates of graceful aging, developed by the researchers were used to gather the data for the study. To determine the perceptions of the respondents on graceful aging, means and standard deviations were computed. The correlate of graceful aging were identified with the use of multiple correlation and regression through stepwise regression. The study revealed that the respondents had positive attitudes towards graceful aging. In addition, significant correlations were found between graceful aging and the following independent variables: self-fulfillment in job assignment, feelings of self worth, degree of closeness with the community, and adequacy of preparation for old age. No significant correlation was found between graceful aging and two other variables: health-status and educational attainment. Self-fulfillment in the job assignment and feelings of self worth were found to be the best predictors of graceful aging. The results suggested the use of the wholistic approach in forming the young religious of the respondents congregation to better prepare them for graceful aging and the offering of enrichment programs to assist the aged members in the pursuit of self-fulfillment. A director of retirement skilled in psychology or counseling may be appointed to meet the spiritual and psychological needs of the aged sisters. Counseling services were also recommended based on the findings of the study.